Beyond the highland mist [compact disc, unabridged] - Moning, Karen Marie (Moning, Karen Marie. Highlander., 2007)
Two modern-day women find themselves hurled back in time to medieval Scotland, where they are entranced and seduced by legendary Highland warriors.